2009
DOI: 10.1074/jbc.m109.029421
|View full text |Cite
|
Sign up to set email alerts
|

Thiolation Controls Cytoplasmic tRNA Stability and Acts as a Negative Determinant for tRNA Editing in Mitochondria

Abstract: Kinetoplastids encode a single nuclear tryptophanyl tRNA that contains a CCA anticodon able to decode the UGG codons used in cytoplasmic protein synthesis but cannot decode the mitochondrial UGA codons. Following mitochondrial import, this problem is circumvented in Trypanosoma brucei by specifically editing the tRNA Trp anticodon to UCA, which can now decode the predominant mitochondrial UGA tryptophan codons. This tRNA also undergoes an unusual thiolation at position 33 of the anticodon loop, the only known … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
53
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(56 citation statements)
references
References 32 publications
3
53
0
Order By: Relevance
“…Tight regulation of tRNA editing might be required if unedited and edited tRNA Trp have non-overlapping functions in translation assigned to UGG and UGA codons, respectively. We have shown that ablation of Mtu1 essentially abolishes thiolation of mitochondrial tRNA Trp , which in agreement with the results by Wohlgamuth-Benedum et al (31) leads to an increase in C to U editing of the wobble nucleotide. However, ablation of Mtu1 did not effect growth of insect stage T. brucei even though the energy metabolism of these cells depends on oxidative phosphorylation and therefore requires mitochondrial gene products.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…Tight regulation of tRNA editing might be required if unedited and edited tRNA Trp have non-overlapping functions in translation assigned to UGG and UGA codons, respectively. We have shown that ablation of Mtu1 essentially abolishes thiolation of mitochondrial tRNA Trp , which in agreement with the results by Wohlgamuth-Benedum et al (31) leads to an increase in C to U editing of the wobble nucleotide. However, ablation of Mtu1 did not effect growth of insect stage T. brucei even though the energy metabolism of these cells depends on oxidative phosphorylation and therefore requires mitochondrial gene products.…”
Section: Discussionsupporting
confidence: 80%
“…It has been suggested that in T. brucei cytosol-specific thio modifications influence the stability of tRNA Glu and tRNA Gln (31). We could confirm this observation in our RNAi cell lines, however, the down-regulation was more variable and less pronounced.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…We have recently shown that in the insect stage of the parasite Nfs is indispensable for thiolation of both cytosolic and mitochondrial tRNAs. Furthermore, thiolation has important implications for cytoplasmic tRNA stability of normally thiolated tRNAs and mitochondrial C to U editing of tRNA Trp (24).…”
mentioning
confidence: 99%